Morphological Heterogeneity of p53 Positive and p53 Negative Nuclei in Breast Cancers Stratified by Clinicopathological Variables - Katrin Friedrich; Volker Dimmer; Gunter Haroske; Wolfdietrich Meyer; Franz Theissig; Berit Thieme; Klaus Dietmar Kunze (Analytical Cellular Pathology)
The study was aimed to detect differences in nuclear morphology between nuclear populations as well as between tumours with different p53 expression in breast cancers with different clinicopathological features, which also reflect the stage of tumour progression. The p53 immunohistochemistry was performed on paraffin sections from 88 tumour samples. After the cells had been localised by means of an image cytometry workstation and their immunostaining had been categorised visually, the sections were destained and stained by the Feulgen protocol. The nuclei were relocated and measured cytometrically by the workstation.